The Impact of Financial Literacy on Personal Financial Decision-Making: A Study with Students - M, Arun Kumar K; Srinivasa, N. (Journal of Research in Vocational Education, 2025)
As students are developing long - term financial habits, financial literacy has been increasingly recognised as an essential skill for effective personal financial management. The objective of this research is to assess the impact of financial literacy on improving students' personal financial decision - makings. Efficient money management is facilitated with the basic understanding of financial concepts which includes budgeting, saving, investing and managing debt. Students who are financially literate tend to make informed decisions in allocation of their resources effectively in order to meet short - term and long - term goals. The study emphasizes the importance of incorporating thorough financial literacy programmes into university curriculum to equip students with vital skills necessary for prudent financial handling. Personal financial management is essential for students as it lays the foundation for their financial well - being both during their academic years and beyond. The need for financial literacy education among students is further underscored with broader economic benefits such as increased savings rate, lower debt levels and improved economic stability. The research explores obstacles in acquiring financial literacy such as socio - economic limitations, lack of practical financial experience and limited access to financial education resources. The data for analyses is collected through questionnaire from 100 respondents using convenience sampling technique to evaluate how financial literacy helps students to make better financial decisions.